A Literature Review on Technology-Based Learning: Trends, Challenges, and Opportunities - Rahman (Indonesian Journal of Education and Science, 2025)
This study synthesizes literature on technology-based learning to identify prevailing trends, implementation challenges, and actionable opportunities across educational levels, with particular attention to Indonesian high schools and Islamic schools. Motivated by rapid digital transformation and uneven adoption during and after the COVID-19 pandemic, the review aimed to answer: What are TEL trends; which barriers hinder effective implementation; and what opportunities can be leveraged to improve teaching and learning through technology? A qualitative systematic literature review was conducted using purposive sampling of 25 publications from 2015–2025 drawn from international and local academic databases. Data were extracted with a structured form and analyzed through thematic content analysis supported by NVivo to generate cross-cutting themes. The review found four dominant trends—artificial intelligence for adaptive learning, mobile and cloud-based platforms for flexible access, immersive XR/AR/VR experiences for experiential learning, and pedagogical innovations such as gamification and flipped classrooms—alongside persistent challenges including infrastructure and access inequities, limited teacher competencies, cultural and organizational resistance, sustainability and scalability concerns, and digital literacy gaps. Corresponding opportunities include personalized learning, expanded access and inclusion, enhanced student engagement through innovative pedagogy, and data-informed strategic planning. The study concludes that TEL is a systemic transformation requiring aligned pedagogy, professional development, equitable infrastructure, and context-sensitive strategies to realize its potential. Future research should empirically assess TEL interventions in classroom settings and explore long-term impacts on equity and learning outcomes.